Development and internal validation of multivariable prediction models for biochemical failure after MRI-guided focal salvage high-dose-rate brachytherapy for radiorecurrent prostate cancer. (September 2021) - Willigenburg, Thomas; van Son, Marieke J.; van de Pol, Sandrine M.G.; Eppinga, Wietse S.C.; Lagendijk, Jan J.W.; de Boer, Hans C.J.; Moerland, Marinus A.; van der Voort van Zyp, Jochem R.N.; Peters, Max
Highlights: Biochemical failure rates after focal salvage high-dose-rate brachytherapy are high. Evidence on predictors for failure is limited to whole-gland salvage radiotherapy. Two prediction models for biochemical failure were developed and internally validated. Based on pre- and post-salvage characteristics we can identify high-risk patients. These models can be used for patient counselling at baseline and during follow-up. Abstract: Background and purpose: Magnetic resonance-guided focal salvage high-dose-rate brachytherapy (FS-HDR-BT) for radiorecurrent prostate cancer (PCa) shows low toxicity rates. However, biochemical failure (BF) after treatment occurs frequently. We developed two prediction models for BF (Phoenix definition) with the aim of enhancing patient counselling before FS-HDR-BT and during follow-up. Materials and methods: A prospective cohort of 150 radiorecurrent PCa patients treated with FS-HDR-BT between 2013 and 2020 was used for model development and internal validation. Multivariable Cox Proportional Hazards regression was applied. For model 1, only pre-salvage variables were included as candidate predictors. For model 2, additional (post-)salvage characteristics were tested. After calibration, nomograms and webtools were constructed. Finally, three risk groups were identified. Results: Sixty-one patients (41%) experienced BF. At baseline (model 1), age, gross tumour volume, pre-salvage PSA, and pre-salvage PSA doubling time (PSADT) were predictive of BF. During follow-up (model 2), age, pre-salvage PSA and PSADT, seminal vesicle involvement, post-salvage time to PSA nadir, and percentage PSA reduction were predictive of BF. The adjusted C-statistics were 0.73 (95% CI: 0.66–0.81) and 0.84 (95% CI: 0.78–0.90), respectively, with acceptable calibration. Estimated 2-year biochemical disease-free survival for the low-, intermediate-, and high-risk groups were 84%, 70%, and 31% (model 1), and 100%, 71%, and 5% (model 2). Conclusion: Two models are provided for prediction of BF in patients with radiorecurrent PCa treated with FS-HDR-BT. Based on pre- and post-salvage characteristics, we are able to identify patients with a high risk of BF. These findings can aid patient counselling for FS-HDR-BT.